Immigrants, ethnic identities and the nation-state - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2012)
In the Western world, multiculturalism has become the way to view and form nationhood, igniting the interest to understand and model identity. The complexity of identity formation, however, has been firm and ethnic and national identities have been deviating more and more. In this paper, we seek to investigate the nature, role and relationships between ethnic and national identities by using migrants as the natural innovators. The arrival of immigrants can amplify social challenges and both natives and immigrants can see their identities altering and evolving. Individuals in a country can be patriotic, nationalistic, indifferent, apathetic, or subvert and undermining. The openness of the people in the host country, their embracing of new cultures and their respect towards newcomers can play a major role in how immigrants react and how close they remain with the country of origin. The laws of the host country together with the ideals, the self-understanding and the foundation of the sovereign nation can also affect the identities of immigrants and natives at the individual level and at the nation-building level. We present empirical results concerning ethnic and national identities and we discuss the ramifications of the divergence between them. We review surveys and experimental contributions to the study of identity formation and its consequences for economic behavior. Before we conclude we debate the endogeneity issue of identity.
Keywords: F22; F52; F54; F59; J15; J16; Z10; 330; international migration; economic nationalism; colonialism; economics of minorities; ethnic identity; national identity; cultural economics